The Greatest story ever told - Steven, George (Quezon City : Viva Video.)
" A magnificent film, handled with reverence, artistic appreciation and admirable restraint" (New York Daily News), this glorious epic is an inspiring, grand -scale recreation of the life of Jesus of Nazareth, from his humble birth and teaching to His crucifixion and ultimate Resurrection. Lavishly produced at a cost of $20 million-an enormous amount for the time -and honored with six 1965 Academy Award nominations, this exceptional motion pictures is exquisitely beautiful. Now fully restored to its original theatrical brilliance with intermission and overture, it is truly The Greatest Story Ever Told.